2016
DOI: 10.1080/00207454.2016.1212855
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aerobic exercise on the structure and function of DMN-related brain regions: a systematic review

Abstract: Physical activity may play a role in both the prevention and slowing of brain volume loss and may be beneficial in terms of improving the functional connectivity of brain regions. But much less is known about the potential benefit of aerobic exercise for the structure and function of the default mode network (DMN) brain regions. This systematic review examines the effects of aerobic exercise on the structure and function of DMN brain regions in human adulthood. Seven electronic databases were searched for pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 55 publications
6
54
0
1
Order By: Relevance
“…A recent meta-analysis revealed that aerobic exercise increases hippocampal volume. 15 However, studies in schizophrenia have found different results for the effects of aerobic exercise on hippocampal structure, probably because the resolution of the acquired structural MRI data was lower and the human brain is subject to high variability in function, structure and response. 92 , 93 , 94 Furthermore, we did not use a randomization procedure to allocate the schizophrenia patients to the endurance training augmented with cognitive remediation or table soccer augmented with cognitive remediation group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis revealed that aerobic exercise increases hippocampal volume. 15 However, studies in schizophrenia have found different results for the effects of aerobic exercise on hippocampal structure, probably because the resolution of the acquired structural MRI data was lower and the human brain is subject to high variability in function, structure and response. 92 , 93 , 94 Furthermore, we did not use a randomization procedure to allocate the schizophrenia patients to the endurance training augmented with cognitive remediation or table soccer augmented with cognitive remediation group.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 , 13 , 14 Some of these studies provided evidence that aerobic exercise increases hippocampal volumes; this was recently confirmed by a meta-analysis. 15 However, there are also findings of no volume increase in the hippocampus 13 or even hippocampal volume decrease in the right hippocampal subfields cornu ammonis (CA)-2/3, subiculum and dentate gyrus (DG) after an intense aerobic intervention. 16 Volume loss correlated negatively with fitness improvement, indicating that decreased hippocampal volume was found mainly in those participants who did not benefit from the exercise program.…”
Section: Introductionmentioning
confidence: 99%
“…Structural changes in certain regions of the brain have been found to follow exercise and are often linked to concomitant changes in cognition; for example, increases in the hippocampus (Lorens-Martín et al, 2009 ; Erickson et al, 2011 ), as well as the anterior cingulate cortex, dorsal lateral prefrontal cortex, and more broadly the prefrontal cortex (ACC, DLPC, and PFC; Gordon et al, 2008 ; Erickson et al, 2011 ; Weinstein et al, 2012 ; Curlik and Shors, 2013 ; Hayes et al, 2013 ; Nishiguchi et al, 2015 ; ten Brinke et al, 2015 ; Jonasson et al, 2017 ; Li et al, 2017 ). While the body of research has been growing with respect to linking physical exercise and cognition via biomarkers, scant literature has yet explored how these indicators and mechanisms react in the case of combined or interactive mental and physical exercise interventions in humans, wherein there might be somewhat differential or compounding beneficial effects given a two-for-one intervention (for a promising exception, see Eggenberger et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing exercise engagement is capable of increasing CRF and has also been shown to enhance brain plasticity in animal models [44,45] and in humans [46][47][48][49]. Higher CRF is also associated with better cognitive performance [50][51][52] and resting state functional connectivity [53][54][55][56] in cross-sectional studies and following exercise interventions.…”
Section: Discussionmentioning
confidence: 99%